100 Cities of the World - Blei, Natalie (2007)
Covering cities from around the world, this work features cities ranging from the biggest metropolis', beautiful cities to the most fascinating capitols. It is illustrated with images and includes facts and files, history and stories, background information and also sightseeing highlights.